Golden boys - Hartnett, Sonya (Candlewick Press, 2016)
Rex and Tabby Jenson and their sons, Colt and Bastian, arrive in Freya Kileys Australian neighborhood with little fanfare, but their presence sends fissures throughout their modest community.